A via crucis do corpo na poética performática de Angélica Freitas e Berna Reale - DANIEL ALMEIDA MACHADO (2021)
The absolute violence that emanates from human relations accompanies us daily, on the news, in daily life and at the heart of our actions. Passive or active beings, we participate in life between violence. Dead-end subjects, we can try to understand violence, to represent it in an aesthetic way. In this sense, the present work aims, through the dialogue between poems by Gaúcho writer Angélica Freitas, in Um útero é do tamanho de um punho, and performances by the visual artist from Pará, Berna Reale, to demonstrate a poetic-artistic-philosophical discourse about violence , especially against female bodies. We will think, therefore, how violence takes shape through literature, the visual arts, and the questioning of thinkers like Hannah Arendt, Judith Butler, Slavoj Žižek, Michel Foucault, Heloisa Buarque de Hollanda and Jacques Derrida.